2016
DOI: 10.4238/gmr.15028083
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and correlation in interspecific and intraspecific hybrids of cotton

Abstract: ABSTRACT. Interspecific and intraspecific hybrids show varying degrees of heterosis for yield and yield components. Yield-component traits have complex genetic relationships with each other. To determine the relationship of yield-component traits and fiber traits with seed cotton yield, six lines (Bt. CIM-599, CIM-573, MNH-786, CIM-554, BH-167, and GIZA-7) and three test lines (MNH-886, V4, and CIM-557) were crossed in a line x tester mating design. Heterosis was observed for seed cotton yield, fiber traits, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…These results suggest that lint percentage has been selected as a major target in the breeding process of elite parents, and that increased lint index combined with decreased seed index are the primary contributors for increased lint percentage (The seed index was the weight of 100 seeds and the lint index was the lint obtained from 100 seeds. Lint percentage = lint weight/seed cotton weight) (Munir et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…These results suggest that lint percentage has been selected as a major target in the breeding process of elite parents, and that increased lint index combined with decreased seed index are the primary contributors for increased lint percentage (The seed index was the weight of 100 seeds and the lint index was the lint obtained from 100 seeds. Lint percentage = lint weight/seed cotton weight) (Munir et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Number of bolls in cotton has been reported to be a major yield contributing feature, affecting the hybrid yield (Zeng and Wu, 2012). The higher number of bolls in the cotton hybrids resulted from the collective effect of both the boll retention and fruiting node (Munir et al ., 2016). Mean values for sowing dates revealed that S1 produced maximum bolls while S4 sowing minimum BP.…”
Section: Discussionmentioning
confidence: 99%
“…Interspecific crosses between upland and Pima cotton produce better fiber traits but disease incidence was a major problem. In contrast, intraspecific hybrids gave stability in production, improved fiber traits, and ensure seed purity [15]. In most cases, positive heterosis is required but for plant height, maturity, and gossypol content negative heterosis is desired in cotton.…”
Section: Introductionmentioning
confidence: 99%